2018
DOI: 10.2196/jmir.9392
|View full text |Cite
|
Sign up to set email alerts
|

Use of Smartphones for Early Detection of Melanoma: Systematic Review

Abstract: BackgroundThe early diagnosis of melanoma is associated with decreased mortality. The smartphone, with its apps and the possibility of sending photographs to a dermatologist, could improve the early diagnosis of melanoma.ObjectiveThe aim of our review was to report the evidence on (1) the diagnostic performance of automated smartphone apps and store-and-forward teledermatology via a smartphone in the early detection of melanoma, (2) the impact on the patient’s medical-care course, and (3) the feasibility crite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 73 publications
(250 reference statements)
0
53
1
2
Order By: Relevance
“…We included an additional two studies2930 that were not included in previous reviews. We also excluded between three42 and five9 studies that reported the development (without independent validation) of new apps that were included in the other two reviews because such studies are likely to overestimate accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…We included an additional two studies2930 that were not included in previous reviews. We also excluded between three42 and five9 studies that reported the development (without independent validation) of new apps that were included in the other two reviews because such studies are likely to overestimate accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several smartphone applications, such as SkinVision, UMSkinCheck, and MoleScope, have been developed with purported goals of wide-spread accessibility, cost-effective screening, and ultimately increased early detection for patients. However, multiple studies have shown that these applications are often inaccurate: 36,37 one study found that 3 out of 4 applications incorrectly classified upwards of 30% of melanomas as low-risk lesions. 37 These applications could be a very useful tool for melanoma diagnosis if accuracy could be improved and if strict regulatory oversight was ensured, 37,38 however, experts caution that reliance on these applications as they are currently available has the potential to harm patients through a false sense of security, potentially resulting in delayed diagnosis.…”
Section: Diagnosis and Prognosis Of Melanomamentioning
confidence: 99%
“…An expense of around 30 euros has just saved a few hundred euros in expenses and a lot of unnecessary stress for both the patient and the care staff in charge of organizing a transfer. There are a large number of published examples of smartphone-based telemedicine demonstrating both its clinical effectiveness and costeffectiveness in fields as varied as geriatrics [21], psychiatry [22], neurology [23], dermatology [24], and cardiology [25].…”
Section: An Example Of How Smartphone-based Telemedicine Could Be Orgmentioning
confidence: 99%